KOMUNIKASI INTERPERSONAL SEBAGAI STRATEGI PENINGKATAN PEMANGFAATAN LAYANAN PERPUSTAKAAN DI ERA DIGITAL - Muhamad Bisri Mustofa; Amelia Rosnaida; Siti Wuryan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Technological advances that are happening today have had a significant impact and progress in various sectors, especially in the field of information and communication. Communication, in its various forms, is one of the aspects affected by these developments, including interpersonal communication. A close relationship between interpersonal communication and libraries can be found. The library, as a building, serves as a place where various activities related to managing, collecting, compiling, organizing, and processing library materials are carried out. Interpersonal communication plays an important role in the context of this library. This study applies qualitative methods in data collection by approaching literature review, namely